Monitoring soil coverage and yield of cowpea furrow irrigated with saline water - Neves, Antonia; Lacerda, Claudivan; Teixeira, Adunias; Costa, Carlos; Gheyi, Hans (Revista Ciência Agronômica, 2010)
Cowpea crop is of great importance for northeast Brazil. The objective of this work was to evaluate the application of saline water in different developing stages on plant growth and changes in soil characteristics, measured by soil coverage, and on yield of cowpea plants. The experiment was conducted under field conditions, during the dry season in a completely randomized block design with five treatments and five replications. Each experimental unit consisted of 4 lines of plants with 5.0 m long. The treatments evaluated were: 1. irrigation with groundwater with electrical conductivity (ECw) of 0.8 dS m-1 during the whole crop cycle; 2. saline water (5.0 dS m-1) during the whole crop cycle; 3, 4 and 5. saline water (5.0 dS m-1) up to 22nd, during 23rd to 42nd and from the 43rd to 62nd days after sowing, respectively, and groundwater in the remaining period. Soil coverage was evaluated by digital images using the software ENVI for image processing and classification. It was found that the continuous use of saline water inhibits plant growth, while irrigation with saline water during germination and initial growth stages caused retardation in plant development, but in this last case a recovery was observed in the final part of the experimental period. For treatments 2 and 3, a reduction was verified in the number of pods and in seed production, as compared to other treatments. Irrigation with saline water during 23 to 42 and 43 to 62 days after sowing did not affect reproductive and vegetative growth, but the saline water application in the pre-flowering (treatment 4) caused anticipation of the reproductive cycle.